Pengaruh Jiwa Wirausaha dan Nilai Wirausaha Terhadap Peningkatan Kemandirian Usaha Melalui Perilaku Wirausaha (Studi Kasus UMKM Di Kecamatan Medan Johor) - Pohan, Fitriani; Hermansyur, H.M; Putra, Rizky (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to determine the effect of entrepreneurial spirit and entrepreneurial value on increasing business independence through entrepreneurial behavior in MSMEs in Medan Johor sub –district. The population in this study wa 583 business actors, and the sampel was 237 respondents using purposive sampling technique. The analysis technique used is multiple regression and path analysis.This research is a type of comparative casual research with a quantitative approach. The result of this study indicate that the variables of entrepreneurial spirit and entrepreneurial value have a significant effect on business independence. The entrepreneurial spirit and entrepreneurial values have a significant effect on entrepreneurial behavior. The entrepreneurial behavior variable has a significant effect on business independence. The entrepreneurial spirit and entrepreneurial values have a significant effect on business independence mediated by entrepreneurial behavior.